QUALITY OF SERVICE AT PUBLIC SERVICE MALL BOYOLALI REGENCY - Cahyani, Devita Indri (Jurnal Ilmu Administrasi Negara, 2024)
The Public Service Mall (MPP) in Boyolali Regency is an innovation aimed at improving service quality. Before the establishment of the Public Service Mall (MPP) in Boyolali Regency, public services were considered less effective and complicated. With the presence of the Boyolali Regency Public Service Mall (MPP), it is hoped that it will provide easy access to the public in terms of government administration. This research uses qualitative descriptive methods. The findings from this research indicate that the quality of service at the Boyolali Regency Public Service Mall (MPP) is considered quite good but needs to be improved. The seven indicators put forward by Gronroos to analyze service quality are professionalism & skills, reputation & credibility, attitudes & behavior, accessibility & flexibility, reliability & trustworthiness, service recovery, and serviscape. Of these indicators, four of them have not reached optimal levels, such as professionalism & skills, attitudes & behavior, accessibility & flexibility, and reliability & trustworthiness. Meanwhile, indicators of reputation & credibility, service recovery and serviscape environment are running well. Therefore, researchers recommend that the Boyolali Regency Public Service Mall (MPP) improve indicators that are not yet optimal, as well as maintain service quality at indicators that are already good.